BATAM VIEW BEACH RESORT: TROPICAL BEAUTY ON THE COAST, BATAM CITY, INDONESIA - Ismi Balqista Ratu Ayunda; Arnita Fetiyani Sangadji Laada; Seprina Crisnawati (PT. Radja Intercontinental Publishing, 2023)
Batam View Beach Resort: Tropical Beauty On The Coast, Batam City, Indonesia There Are 4 Conclusions As Follows: 1) Bioregionalism Draws Inspiration From Traditional Building Approaches From Malay And Vernacular Architecture. 2) These Traditional Building Forms Of Malay Culture Indicate How Deep-Rooted Cultures Have Naturally Evolved Appropriate Lifestyles Adapted To Their Particular Physical Environment. 3) Ecocultural Logic Emphasizes The Preservation Of Various Built Cultural Archetypes, Combined With A Concern For Cultural Continuity Expressed Through The Transformation And Reuse Of Traditional Construction Techniques, Building Typologies, And Settlement Patterns, Each With A Local History Of Evolution And Use.4) Emphasis On The Specificity Of Place, Use Of Local Materials, And Appropriate Formal Response To Climatic And Climatic Conditions